Map reading: a pending competence at the tourism students? - Parreño-Castellano, Juan Manuel; Rodríguez-Rodríguez, Mercedes; González-Herrera, Manuel Ramón; Jiménez-Barrado, Víctor (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Map reading is a pending skill for college students. That is the case of the students of the Degree in Tourism from the universities of Las Palmas de G.C., in Spain, and Autónoma de Juárez, in Mexico, who use maps to understand the tourist reality without having acquired sufficient cartographic literacy. This communication presents a diagnosis of the geographical thinking of these students focused on the abilities of location, interpretation, and relational analysis of territorial variables. It has been confirmed that they only reach a descriptive level and that it is necessary to implement specific didactic strategies.